1996
DOI: 10.1111/j.1469-8137.1996.tb01905.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of a CO2‐concentrating mechanism in Emiliania huxleyi

Abstract: The development of an inorganic carbon concentrating mechanism (CCM) in relation to the expression of extracellular carbonic anhydrase (CA^.^.^) in cells from the stationary phase of Emiliania huxleyi cultures was investigated. Unlike exponential phase cells, those in the stationary phase showed a high affinity for CO,; the K(i.-[CO,,] (i.e. the CO, concentration required for half-maximal rate of photosynthesis) was 1-6//M at pH 8-3. Measurement of the internal inorganic carbon concentration by the silicone oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In addition to observations of CA activity, laboratory studies showed that diverse marine phytoplankton have CCMs (Burns & Beardall 1987, Nimer & Merrett 1996. CCMs were described for even tiny picoeukaryotic marine phytoplankton (<2 μm) in which the diffusion of CO 2 is not expected to limit photosynthesis (Iglesias-Rodriguez et al 1998, Giordano et al 2005.…”
Section: Ccms In Marine Phytoplanktonmentioning
confidence: 97%
“…In addition to observations of CA activity, laboratory studies showed that diverse marine phytoplankton have CCMs (Burns & Beardall 1987, Nimer & Merrett 1996. CCMs were described for even tiny picoeukaryotic marine phytoplankton (<2 μm) in which the diffusion of CO 2 is not expected to limit photosynthesis (Iglesias-Rodriguez et al 1998, Giordano et al 2005.…”
Section: Ccms In Marine Phytoplanktonmentioning
confidence: 97%
“…Recent studies, however, provide clear evidence for active carbon uptake in E. huxleyi (e.g. Nimer and Merret 1996;Rost et al 2002Rost et al , 2003. The efficiency of the CCM employed by E. huxleyi appears to be low when compared to other phytoplankton taxa (e.g.…”
Section: Photosynthesis and Growthmentioning
confidence: 99%
“…Evidence for the presence of CA(s) has been found in all unicellular microorganisms from freshwater to marine environments, including Chlorophyceae (Ramazanov et al, 1993(Ramazanov et al, , 1994Sültemeyer et al, 1995), Bacillariophyceae (Rotatore et al, 1995;Sültemeyer et al, 1993), Rhodophyceae (Aizawa & Miyachi, 1986), and Haptophyceae (Nimer & Merrett, 1996). In prokaryotes, Synechocystis PCC6803 and PCC7942 contains three potential CA genes, i.e., icfA, ecaA, and ecaB.…”
Section: Introductionmentioning
confidence: 99%